Ethics in global health outreach: three key considerations for pharmacists. (15th April 2014) - Romo, Matthew L.; DeCamp, Matthew
Abstract Objective The objective of this article is to explore three key ethical tenets that pharmacists should consider prior to participating in global health outreach. Key findings There are increasing opportunities for pharmacists to be involved in global health outreach; however, little attention has been given to the ethical issues that participation may raise for pharmacists. Pharmacists' widely accepted and basic ethical obligations at home lay the foundation for effective management of these ethical challenges abroad. At home, pharmacists have an ethical obligation to provide the best possible quality of care to the patients for whom they serve. During global health outreach, this involves identifying and mitigating the potential for harm, as well as understanding and respecting cultural differences. Furthermore, pharmacists have an ethical obligation to not only meet individual patient needs, but also community and societal needs, when applicable. In global health outreach, this involves tailoring interventions to the needs of the population served. Conclusions Because of their unique skillset, pharmacists have the potential to make significant contributions to global health. Applying ethical principles, such as providing the best possible care, respecting cultural differences and meeting societal needs, provides the foundation for successful global health outreach by pharmacists.